Pengembangan Media Pembelajaran Powerpoint Interaktif Materi Ikatan Kimia Berbasis Scientific Approach Untuk Menumbuhkan Literasi Kimia Peserta Didik - Mesi Sepuh Utami; Afrida; Asmiyunda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to find development process, determine the feasibility according to material and media experts, teacher assessment, and studens responses to interactive powerpoint media based on scientific approach to foster students chemical literacy developed. The research method used is research and development (R&D) with the development model of Lee & Owens (2004) which includes 5 stages, namely analysis, design, development, implementation, and evaluation. The research was conducted in a small group trial with 10 students at SMAN 10 Muaro Jambi. Data analysis using qualitative and quantitative methods. The results of the study showed that the interactive powerpoint media based on the scientific approach that was developed was declared feasible and valid with an average score of material and media validation of 4,85 and 4,86, an average score of teacher assessment of 4,93, the result of the small group trial scored 690 with a percentage of 92%. Then the result of the students results, the interactive powerpoint media developed was declared feasible and valid for use in learning with positive responses from students.